A New Nondestructive Test Equipment Based On Image Processing and Magnetic Flux Analysis - Buyuksahin, Utku; Kirli, Ahmet (TRANS TECH PUBLICATIONS LTD, 2012)
Nondestructive testing (NDT) methods has been increased within recent years depending on the needs of industry, parallel to new technological developments. Many studies have focused on thermal imagining, magnetic flux analysis or both, which are used in order to detect the deformation on surface and under the surface. In this study a new technique is suggested to eliminate the perturbations which are distorting effects of one point cameras' in terms of perspective. A new integration is also proposed in this research such as using image recognition with magnetic flux analysis. Taking advantage of this integration and the new approach to image processing, both the surface and the inside of a mechanical product can be tested properly.
Keywords: Nondestructive Testing; Image Processing; Magnetic Flux Analysis; VISUAL INSPECTION; RECOGNITION; CONCRETE; Engineering; Materials Science